2018
DOI: 10.1002/ejic.201800126
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphazenes – Synthetically Versatile Block Copolymers (“Multi‐Tool”) for Self‐Assembly

Abstract: This microreview outlines recent advances on the synthesis and self-assembly of polyphosphazene diblock copolymers, a class of versatile polymers (Multi-Tool) able to generate a great variety of different well-defined nanomorphologies. Particular focus is placed on the synthesis of linear block copolymers composed of two polyphosphazene chains (PP-b-PP′), or hybrid polymers combining one PP chain with a non- [a] 2484 Gabino A. Carriedo (Ph D in 1981) is Full-time Professor of Inorganic Chemistry in the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 238 publications
0
9
0
Order By: Relevance
“…This can be carried out in one pot directly from PCl 3 (Figure 3A), hence without tedious purification of the intermediates [16], which is suitable for upscaling, albeit with some loss of control. More recently, it has been shown that starting from Ph 3 PCl 2 , monodirectional growth can be ensured [17], as shown in Figure 3B, which is a feature that opens the door to the development of chain-end functionalized polyphosphazenes [18], as well as higher architectures such as polyphosphazene block copolymers [19], block copolymers with organic macroinitiators [20], and star-branched and bottle-brush polyphosphazenes [21]. Similarly, the development of controlled routes to polyphosphoesters has led to a recent surge in their development [22].…”
Section: Controlled Polymerization Routesmentioning
confidence: 93%
See 1 more Smart Citation
“…This can be carried out in one pot directly from PCl 3 (Figure 3A), hence without tedious purification of the intermediates [16], which is suitable for upscaling, albeit with some loss of control. More recently, it has been shown that starting from Ph 3 PCl 2 , monodirectional growth can be ensured [17], as shown in Figure 3B, which is a feature that opens the door to the development of chain-end functionalized polyphosphazenes [18], as well as higher architectures such as polyphosphazene block copolymers [19], block copolymers with organic macroinitiators [20], and star-branched and bottle-brush polyphosphazenes [21]. Similarly, the development of controlled routes to polyphosphoesters has led to a recent surge in their development [22].…”
Section: Controlled Polymerization Routesmentioning
confidence: 93%
“…The higher stability compared to liposomes renders them ideal drug carriers [54]. Furthermore, Soto and coworkers have developed, amongst other nanomorphologies [19], giant polymersomes, so-called giant unilamellar vesicles (GUVs) with good stability over a long time range [57]. Giant polymersomes (approximately 10-100 µm) and GUVs (>1 µm) as opposed to standard polymersome sizes in the region of 100 nm diameters are of special interest due to their similar size to cells making them better suited to the biomimicry of cellular processes.…”
Section: Polymersomesmentioning
confidence: 99%
“…Since polyalkylphosphazenes are not sensitive to hydrolysis due to their stable P–C bonds, morphological changes occur without degradation of the polymer. A recent review article describes the advances in the field of self‐assembly of this family of polymers …”
Section: Ph‐responsive Polymersmentioning
confidence: 99%
“…Selective protonation of polyphosphazene block copolymers induces rapid self‐assembly. Reproduced from ref and adapted from original work in ref …”
Section: Ph‐responsive Polymersmentioning
confidence: 99%
“…Polyphosphazene is a unique class of hybrid polymers with an amazing structural design. [ 1,2 ] It has a wide range of applications in high‐performance elastomers such as low‐temperature elastomers, [ 3–5 ] flame‐retardant materials, [ 6–8 ] stretchable electronics, [ 9,10 ] bionic muscles, [ 11,12 ] super‐hydrophobic materials, [ 13,14 ] and biodegradable materials. [ 15–17 ] However, there are few reports about recyclable and self‐healing polyphosphazene, while similar studies are popular in polysiloxane.…”
Section: Introductionmentioning
confidence: 99%